Examining the Factors Affecting Accounting Prudence - Mukhammad Idrus; Siti Fatimah; Afiah Mukhtar; Karta Negara Salam (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study examines the effect of managerial ownership, firm size, leverage, and growth opportunities on accounting prudence. This type of research includes causal research using quantitative methods. The population in this study were all mining companies listed on the BEI, as many as 28 companies. The sample in this study was determined by purposive sampling, so the full selection was 50 data from 10 financial statements of mining companies for five years. Secondary data was collected through the Indonesia Stock Exchange website and analyzed using Multiple Regression Analysis with the Ordinary Least Square model using the Eviews Version 12 software. The results found that managerial ownership positively and significantly affected accounting prudence. Meanwhile, firm size and leverage have no significant positive effect on accounting prudence. Meanwhile, the growth opportunities variable has a negative and significant impact on accounting prudence. The suggestions given by the author for further research are expected to consider other factors outside of this research that can affect accounting prudence such as litigation risk, taxes, and public ownership and can expand objects to other sectors and extend the research period to provide better results and more accurate.